Electronic structure by X-ray absorption spectroscopy and observation of field induced unusually slow spin relaxation from magnetic properties in pyrochlore Eu2−xFexTi2O7 - Pal A.; Ghosh S.; Kumar S.; Schwier E.F.; Sawada M.; Shimada K.; Gupta M.; Phase D.M.; Ghosh A.K.; Chatterjee S. (My University, 2025)
X-ray absorption spectroscopy (XAS) and magnetization of hybrid pyrochlore Eu2-xFexTi2O7 (EFTO) were investigated, where the rare earth Eu (4f) was replaced with transition metal Fe (3d) to introduce competing 4f-3d interactions. It is confirmed that the valence states of Eu and Fe ions are formally trivalent while that of Ti ions are tetravalent (3d0). The analysis yielded that the tetravalent Ti ions occupy octahedral sites with distorted Oh symmetry which is triggered by the presence of vacant 8a anionic site adjacent to TiO6 octahedra. Further study with Fe doping revealed that it essentially reduces the octahedral distortion by introducing anionic disorder (migration of 48f oxygen ions to 8a site). Analysis of O K edge XAS spectra further confirmed the Fe substitution causing the systematic change in the ligand (O2−) coordination of the Ti4+ cations. Interestingly, a new field induced transition at low temperature T* (4 K < T* < 8 K) associated with unusually slow spin relaxation was observed. The transition shifted towards higher temperatures both with increasing applied field and Fe concentration. However, the single ion spin freezing (Tf ∼ 35 K) appears to be largely suppressed with Fe substitution. Moreover, dc magnetization data showed rise of ferromagnetic contribution below 100 K. © 2018